PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN, DAN CITRA MEREK TERHADAP NIAT BELI ULANG JASA TRANSPORTASI P.O SIMPATI STAR DI KOTA BANDA ACEH - Regi Miranda; Nurdasila Nurdasila (Departemen Manajemen, 2020)
This study aims to measure “the effect of service quality, trust, and brand image on repurchase intentions on P.O Simpati Star transportation services in the city of Banda Aceh” the sample used in this study was the users of P.O Simpati Star transportation services in the city of Banda Aceh, amounting to 180 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used was purposive sampling. Multiple linear regression is used as a method of analysis to determine the effect of all the variables involved. Based on the results of multiple linear regression analysis, it indicates that service quality, trust, and brand image have a positive effect on repurchase intentions